Biomaterial and Biofilm Interactions with the Pulp-Dentin Complex-on-a-Chip. (September 2021) - Rodrigues, N.S.; França, C.M.; Tahayeri, A.; Ren, Z.; Saboia, V.P.A.; Smith, A.J.; Ferracane, J.L.; Koo, H.; Bertassoni, L.E.
Calcium silicate cements (CSCs) are the choice materials for vital pulp therapy because of their bioactive properties, promotion of pulp repair, and dentin bridge formation. Despite the significant progress made in understanding CSCs' mechanisms of action, the key events that characterize the early interplay between CSC-dentin-pulp are still poorly understood. To address this gap, a microfluidic device, the "tooth-on-a-chip, " which was developed to emulate the biomaterial-dentin-pulp interface, was used to test 1) the effect of CSCs (ProRoot, Biodentine, and TheraCal) on the viability and proliferation of human dental pulp stem cells, 2) variations of pH, and 3) release within the pulp chamber of transforming growth factor–β (TGFβ) as a surrogate of the bioactive dentin matrix molecules. ProRoot significantly increased the extraction of TGFβ ( P < 0.05) within 24 to 72 h and, along with Biodentine, induced higher cell proliferation ( P > 0.05), while TheraCal decreased cell viability and provoked atypical changes in cell morphology. No correlation between TGFβ levels and pH was observed. Further, we established a biofilm of Streptococcus mutans on-chip to model the biomaterial-biofilm-dentin interface and conducted a live and dead assay to test the antimicrobial capability of ProRoot in real time. In conclusion, the device allows for direct characterization of the interaction of bioactive dental materials with the dentin-pulp complex on a model of restored tooth while enabling assessment of antibiofilm properties at the interface in real time that was previously unattainable.